2004
DOI: 10.1890/03-4043
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Scale in Ecology: Lessons From Awave‐swept Shore

Abstract: Understanding the role of scale is critical to ecologists' ability to make appropriate measurements, to ''scale up'' from local, short-term experiments to larger areas and longer times, to formulate models of community structure, and to address important conservation problems. Although these issues have received increased attention in recent years, empirical measurements of the scales of ecologically important variables are still rare. Here, we measure the spatial and temporal scales of variability of 15 ecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
132
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(134 citation statements)
references
References 53 publications
2
132
0
Order By: Relevance
“…Denny et al (2004), for example, found that the variance of several physical and biological variables measured along a stretch of rocky coast in California increased with increasing spatial scale. Denny et al (2004) suggested that the topography of the substratum may affect scaling relationships in intertidal habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Denny et al (2004), for example, found that the variance of several physical and biological variables measured along a stretch of rocky coast in California increased with increasing spatial scale. Denny et al (2004) suggested that the topography of the substratum may affect scaling relationships in intertidal habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests much of the variation is caused by diVerences in wave exposure, which is known to be of profound inXuence on rocky intertidal communities (Ricketts et al 1985;Denny and Wethey 2001;Davis et al 2002;Denny et al 2004). The Mantel test identiWed three variables that together best explain the distribution of species observed: mean signiWcant wave height, surf zone width, and the transect length.…”
Section: # Of Speciesmentioning
confidence: 99%
“…Recurrent analogous findings suggest that relevant variation at spatial scales of tens-hundreds of centimetres up to tens-hundreds of metres is a common feature of a wide range of benthic organisms, habitats and geographic areas (Underwood and Chapman, 1996;Kendall and Widdicombe, 1999;Fraschetti et al, 2005b;Terlizzi et al, 2007;Bertocci et al, 2012), often explained primarily with the effects of the topography of the substratum (e.g. Denny et al, 2004). In sabellariid reefs, small-scale heterogeneity could be due to the availability of different microhabitats formed by worms, hence tubes, of a range of sizes.…”
Section: Discussionmentioning
confidence: 87%